Strategi Meningkatkan Kualitas Pelayanan Pada Departemen Makanan dan Minuman Hotel Episode Kuta Bali - Desi, Ni Luh Ayu Bela; Nugraha, Gede Putra (STKIP AGAMA HINDU SINGARAJA, 2024)
The aim of this research is to identify the challenges and initiatives undertaken by the food and beverage service department at the Episode Kuta Bali hotel to improve service quality and achieve customer satisfaction. The methodology used in this research is qualitative and descriptive, which involves collecting data through observation, interviews and documentation. The main source of information in this research is the Bulung Restaurant and Pool Bar Supervisor in Episode Kuta Bali. The results of this research show that (1) There are still many obstacles experienced in making customers feel satisfied with the facilities and services provided by restaurants. (2) Create new strategies to expand market share in order to improve service quality and customer satisfaction.